WORKING CAPACITY FOR PERSONS WITH MUSCULOSKELETAL DISORDERS - Barone, Līga; Atstāja, Dzintra; Zakriževska-Belogrudova, Maija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Musculoskeletal disorders (MSDs) are prevalent globally and result in substantial personal distress and significant social expenses for businesses and society. The ageing population and labor shortages exacerbate these effects. The aim of this study is to investigate the impact of MDS on employment absenteeism and presenteeism. Two instruments, the EQ-5D and the iPCQ, were used to quantitatively survey the Latvian population. 949 respondents of working age were surveyed. From this group, 553 respondents with MSD were selected, averaging 47 years old, 50.6% of whom were men. The results showed that 7.23% experienced absenteeism in the last month. Additionally, 45.9% reported discomfort at work due to MSDs. The EQ-5D-5L questionnaire revealed a decline in health-related quality of life with increasing age, highlighting the significance of addressing the aging workforce and promoting health preservation. 38.3% of respondents with MSDs received rehabilitation interventions, which showed a moderate association with health-related quality of life. The study showed that there is a negative correlation between health-related quality of life and productivity loss. This highlights the importance of comprehensive interventions that address both the physical and psychological aspects of MSDs. The findings offer valuable insights for policymakers, employers, and healthcare professionals to design targeted interventions that improve the health and productivity of individuals with MSDs.